Entry into marriage and the transition to adulthood among recent birth cohorts of young adults in the United States and the Federal Republic of Germany - James C. Witte (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
Pattems of entry into first marriage among recent birth cohorts (1952 - 1967) of young adults are examined based upon the U.S. Census Bureau 's Survey of Income and Program Participation (SIPP) and the German Socio-Economic Panel (SOEP). This paper attempts to illustrate the manner in which young adults' educational and employmeni histories influence the timing oftheir entry into marriage. Labor force integration - concluding one's education and entering the labor force - is treated as the dominant life course process. Though the paper is primarily descriptive and exploratory, it does reveal several interesting developments: the tendency for American men and women to enter marriage early, relative to their West German peers, continues at the same time as the average age of men and women upon entry into first marriage increases in both countries. Moreover, the rising age at first marriage cuts across all education levels. Thus, the populär notion that increases in average age at first marriage may be attributed to people remaining in school longer is, by itself insufficient. Finally, contrary to Claims that disorderly pattems of transition to adulthood have undermined the traditional pattern of transition (completion of Schödling, entry into the work force and then marriage), the majority of men and women in both countries continue to follow the traditional path.
Keywords: 330